Pyrolysis of high-ash sewage sludge: Thermo-kinetic study using TGA and artificial neural networks - Naqvi, S.R. (Elsevier Ltd, 2018)
Pyrolysis of high-ash sewage sludge (HASS) is a considered as an effective method and a promising way for energy production from solid waste of wastewater treatment facilities. The main purpose of this work is to build knowledge on pyrolysis mechanisms, kinetics, thermos-gravimetric analysis of high-ash (44.6) sewage sludge using model-free methods & results validation with artificial neural network (ANN). TG-DTG curves at 5,10 and 20 Â°C/min showed the pyrolysis zone was divided into three zone. In kinetics, E values of models ranges are; Friedman (10.6â306.2 kJ/mol), FWO (45.6â231.7 kJ/mol), KAS (41.4â232.1 kJ/mol) and Popescu (44.1â241.1 kJ/mol) respectively. ÎH and ÎG values predicted by OFW, KAS and Popescu method are in good agreement and ranged from (41â236 kJ/mol) and 53â304 kJ/mol, respectively. Negative value of ÎS showed the non-spontaneity of the process. An artificial neural network (ANN) model of 2 * 5 * 1 architecture was employed to predict the thermal decomposition of high-ash sewage sludge, showed a good agreement between the experimental values and predicted values (R2 â©¾ 0.999) are much closer to 1. Overall, the study reflected the significance of ANN model that could be used as an effective fit model to the thermogravimetric experimental data. Â© 2018 Elsevier Ltd